Future Studies of Tourism Development Planning (Case study: Ardabil province) - hossein nazmfar; ameneh alibakhshi (تحقیقات کاربردی علوم جغرافیایی)
Tourism is one of the most important means of development in the world. Many countries in the world pay special attention to tourism as an effective tool for their political, cultural and economic development in their country's policies and programs. The present study was carried out in order to plan tourism in Ardebil province based on a futuristic study method. The present research is applied in a practical way as a combination of documentary and survey methods based on a futuristic approach. The research area of Ardabil province and the statistical population is 45 tourism experts, urban and regional planning and executive agencies of the province. Delphi method, cross-effects matrix (Wizard scenario software) and Wizard scenario software were used to analyze the data. Based on the findings of the Delphi method and environmental scanning, 88 factors were identified as influential factors in the development of tourism in Ardebil. In the second step, using the Micmac method, 14 key Factors, including the comprehensive tourism plan, the media, stimulus policies, macro policies of the state, distribution of facilities, infrastructure, recreational centers, increased private incentive to invest in the region, the region's susceptibility to Investment in tourism, planning, security facilities, budget, the existence of hot and mineral water springs, improvement of information systems, such as site and blog, have been identified as key to the development of Ardebil province. In the third step, based on key factors, believable futures were explained using the Wizard scenario method, which ultimately resulted in three strong, weak and believable scenarios. In this scenario, believable scenarios are due to the intermediate between scenarios Strong and weak, have been based on analysis. Accordingly, there are three scenarios named "Golden scenario", " believable scenario" and "Disaster scenario" for the future of tourism in Ardebil province.